Using genetically modified extracellular vesicles as a non-invasive strategy to evaluate brain-specific cargo. (February 2022) - Rufino-Ramos, David; Lule, Sevda; Mahjoum, Shadi; Ughetto, Stefano; Cristopher Bragg, D.; Pereira de Almeida, Luís; Breakefield, Xandra O.; Breyne, Koen
Abstract: The lack of techniques to trace brain cell behavior in vivo hampers the ability to monitor status of cells in a living brain. Extracellular vesicles (EVs), nanosized membrane-surrounded vesicles, released by virtually all brain cells might be able to report their status in easily accessible biofluids, such as blood. EVs communicate among tissues using lipids, saccharides, proteins, and nucleic acid cargo that reflect the state and composition of their source cells. Currently, identifying the origin of brain-derived EVs has been challenging, as they consist of a rare population diluted in an overwhelming number of blood and peripheral tissue-derived EVs. Here, we developed a sensitive platform to select out pre-labelled brain-derived EVs in blood as a platform to study the molecular fingerprints of brain cells. This proof-of-principle study used a transducible construct tagging tetraspanin (TSN) CD63, a membrane-spanning hallmark of EVs equipped with affinity, bioluminescent, and fluorescent tags to increase detection sensitivity and robustness in capture of EVs secreted from pre-labelled cells into biofluids. Our platform enables unprecedented efficient isolation of neural EVs from the blood. These EVs derived from pre-labelled mouse brain cells or engrafted human neuronal progenitor cells (hNPCs) were submitted to multiplex analyses, including transcript and protein levels, in compliance with the multibiomolecule EV carriers. Overall, our novel strategy to track brain-derived EVs in a complex biofluid opens up new avenues to study EVs released from pre-labelled cells in near and distal compartments into the biofluid source.